Tabanidae (Diptera) of Peru: checklist update and description of three new species - Henriques, Augusto Loureiro (2020)
We provide an update to the list of the species of Tabanidae known from Peru, along with descriptions of three new species: Diachlorus tenuimaculatus n. sp., Stenotabanus (Stenotabanus) carrascoi n. sp. and Stenotabanus (Stenotabanus) chaineyi n. sp., bringing to 233 the species of Tabanidae now known from Peru. ________________________________________________________________Publicación registrada en Zoobank/ZooBank article registered:LSIDurn:lsid:zoobank.org:pub:405FCB11-B80B-459A-B7EB-F3E3F7584070Acto nomenclatural/nomenclatural act:Diachlorus tenuimaculatus Henriques & Krolow, 2020LSIDurn:lsid:zoobank.org:act:B3AC891B-5D06-4299-987B-A8E64F7BED8EActo nomenclatural/nomenclatural act:Stenotabanus carrascoi Henriques & Krolow, 2020LSIDurn:lsid:zoobank.org:act:2E008A63-C2B1-4187-AD36-AE183C360E34Acto nomenclatural/nomenclatural act:Stenotabanus chaineyi Henriques & Krolow, 2020LSIDurn:lsid:zoobank.org:act:CCCE2364-1971-4E1F-8E89-E1B120A95BFF________________________________________________________________